Push–Pull Distyryl Boron Dipyrromethenes as Near‐Infrared Sensitizers for Dye‐Sensitized Solar Cells. Issue 10 (9th August 2017) - Shi, Wen‐Jing; Kinoshita, Takumi; Ng, Dennis K. P.
Abstract: A diiodo distyryl boron dipyrromethene (BODIPY) with an ethyl ester group at the meso position was prepared. This compound underwent palladium‐catalyzed Sonogashira cross‐coupling reactions with 4‐(diphenylamino)phenylethyne and 4‐(dimethylamino)phenylethyne to give the corresponding dialkynyl derivatives. After alkaline hydrolysis and acidic work‐up, all three compounds were converted to the carboxyl analogues, which could bind to the surface of TiO2 for application in dye‐sensitized solar cells (DSSCs). These compounds, in particular the dialkynyl analogues, possessed a push–pull structure and a highly conjugated π system, which shifted the Q band to the near‐infrared region. Electrochemical studies revealed that they had appropriate HOMO and LUMO levels for the construction of DSSCs comprising a TiO2 electrode and an electrolyte containing an I3 − /I − redox couple. The optimized structures, frontier molecular orbitals, and absorption spectra of these sensitizers were calculated using density functional theory. The diiodo distyryl BODIPY‐based DSSC showed a photovoltaic conversion efficiency of 2.78 % under AM 1.5G standard sunlight and a maximum incident photon‐to‐current conversion efficiency (IPCE) of >45 % at 780 nm. The DSSCs fabricated with the dialkynyl distyryl BODIPYs could achieve an IPCE value of approximately 20 % at 840 nm and a broader photoresponse over the whole visible range extending up to approximately 950 nm in the near‐infrared region. Abstract : Catch some rays : A series of push–pull‐type distyryl boron dipyrromethenes were synthesized and characterized. Having extended π systems, these compounds serve as sensitizers for dye‐sensitized solar cells with photovoltaic conversion efficiencies of up to 2.78 % under AM 1.5G standard sunlight and broad photoresponses over the whole visible range extending to around 950 nm in the near‐infrared region.